Alat Pengering Dan Pengukur Kadar Air Pada Gabah Berbasis Mikrokontroler - Rizal Ariska Budiawan; Wisnu Wendanto (STIE AUB Surakarta, 2015)
In today's world of electronics and control progressed very rapidly and so quickly revolutionized through the means or medium. Electronics technology also provides a kind of contribution to human life by the very rapid development in this field. Along with the uncertain weather changes that occur, use dryer facilities which can certainly save time and effort. In this moment to try to create a tool which is the application of the system design, ie a grain dryers that use moisture sensors and temperature sensors, as well as using a dryer. This tool created by the end of the process under the appliance door will open itself automatically. With the drier and measuring the water content aimed at speeding up the drying time of the rainy season and can be performed continuously without having an effect on the weather, and can help alleviate human tasks, especially in drying grain.Keywords: Dryers and gauges, water content, grain